Impact of Introducing Triage Criteria for Express Testing at a Canadian Sexually Transmitted Infection Clinic. Issue 11 (November 2015) - Gratrix, Jennifer; Bergman, Joshua; Brandley, Judith; Parker, Penny; Smyczek, Petra; Singh, Ameeta E.
Abstract : Abstract: The implementation of express testing in an sexually transmitted infection (STI) clinic reduced the length of visit time compared with other visit types and increased the proportion of STIs diagnosed at clinic visits. Express testing did not impact the time to treatment for asymptomatic patients diagnosed as having an STI. Abstract : The implementation of express testing in a Canadian sexually transmitted infection clinic reduced patient visit time and did not impact the time to treatment for patients diagnosed as having a sexually transmitted infection.